Indications for Aortic Arch Intervention. (December 2016) - Al-Atassi, Talal; Khoynezhad, Ali
Surgery of the aortic arch is arguably one of the most complex areas of cardiac surgery. Despite that, studies and guidelines have not sufficiently addressed the aortic arch specifically. In general, indications for aortic arch intervention parallel those of the ascending aorta. Herein we review indications for aortic arch intervention in various aortic pathologies based on the scant evidence available combined with surgical expertise and expert opinion.